ANALYSIS OF INPUT EFFICIENCY AND ECONOMIES OF SCALE IN SALT PRODUCTION IN BULELENG REGENCY - Ketut Dyana Novita Sari; Ni Luh Karmini (Adisam Publisher, 2025)
Indonesia, widely recognized as a maritime country with vast marine potential, has yet to achieve salt self-sufficiency despite its favorable geographical conditions. This study aims to analyze the efficiency of input utilization and economies of scale in salt production in Buleleng Regency, one of the main salt-producing regions in Bali Province. A quantitative approach using an associative method and the Cobb-Douglas production function model was employed to examine the influence of capital, labor, land area, and technology on salt production. The sample consisted of 126 traditional salt farmers selected using proportionate stratified random sampling. The results indicate that all input variables—capital, labor, land area, and technology—have a positive and significant effect on production, both partially and simultaneously. Salt production in Buleleng exhibits increasing returns to scale, suggesting potential for output expansion if inputs are optimized. The efficiency analysis reveals that capital, land area, and geomembrane technology are not yet utilized optimally (Ef > 1), while labor is used excessively (Ef < 1). Additionally, the production process is highly dependent on weather conditions, as all salt farmers can only operate during the dry season. These findings underscore the importance of improving access to technology and enhancing input management efficiency to support increased productivity and national salt self-sufficiency.